THE NURSING PROFESSIONAL OF THE HEALTH STRATEGY OF FAMILY FACING POSTPARTUM DEPRESSION - Mendes do Amaral, Maria Thereza; Brinco de Souza, Rachel (Health and Society, 2021)
Care in Primary Health Care for women in the pregnancy-puerperal cycle must take place in an integral way, with individualized care that considers the life history, feelings and the environment in which the woman lives, seeking her physical and mental well- being to prevent postpartum depression. Given this fact, a postpartum consultation is recommended as essential by the Ministry of Health for the early detection of preventable complications common in the period, such as puerperal depression (BRAZIL, 2012). It is known that each woman has a way of reacting to the postpartum due to the different situations that occur, such as the relationship with her partner and her family, her social and cultural life, meaning that, each pregnancy is a unique and individual experience. . (SARMENTO, SETÚBAL, 2012). Therefore, we will address the relationship between nurses and postpartum depression in family health strategies in a city in the state of Rio de Janeiro. It will be a qualitative, descriptive and exploratory study, whose overall objective is to analyze how nurses perform to postpartum women with postpartum depression. OBJECTIVE: The objective of this study is to find out about the role of nurses in Family Health Strategies (FHS) in the city of Valença, RJ. METHOD: This is a descriptive and exploratory study, with a qualitative approach. There are 19 ESFs in the municipality, but 9 strategies were selected, however only 5 wanted to participate. A Google Forms form was sent along with the Free and Informed Consent Form to the email of the selected nurses, but only 5 were returned. Data was collected through a semi-structured interview. RESULTS: Through the data gathered, it was seen that nurses have difficulties in identifying the signs and symptoms of PPD, as well as an approach due to the difficulties encountered both because of the non- adherence of pregnant women in prenatal consultations, which makes it difficult for these pregnant women to adhere to postpartum consultations at the unit and the nurses’ work routine, which makes tracking difficult. The use of the Edinburgh Postnatal Depression Scale is being questioned. CONCLUSIONS: With the lack of adherence of these puerperal women in the consultations, it is very difficult to identify the signs and symptoms of Postpartum Depression, the nurse must seek the population closer to the unit in carrying out health education in the strategy, creating bonds besides giving the postpartum autonomy over their care. The professional must work together with their team in the actions of permanent education, thus, empowering community health workers in the identification, therefore this professional brings the community closer to the strategy, which facilitates users’ adherence to the health service.